Assessing efficacy in myelofibrosis treatment: a focus on JAK inhibition. Issue 6 (December 2012) - Komrokji, Rami; Verstovsek, Srdan
Myelofibrosis (MF) is characterized by splenomegaly, anemia and a debilitating symptom burden (e.g., fatigue, night sweats, pruritus, bone and muscle pain, undesired weight loss). Moreover, these symptoms impair activities of daily living and quality of life. Until recently, there have been no approved therapies for MF, and management of MF has been predominantly palliative. Dysregulated JAK-STAT signaling is associated with the pathologic MF disease state. A novel class of therapies, the JAK inhibitors, offers the potential to abrogate this pathologic signaling pathway. In clinical trials of patients with intermediate- and high-risk MF, JAK inhibitors have demonstrated efficacy in reducing splenomegaly and MF-associated symptoms. Evidence from ruxolitinib trials also suggests that JAK inhibitors may improve survival outcomes.